LAS FÓRMULAS DIPLOMÁTICAS LATINAS EN EPIGRAFÍA - Domínguez Sánchez, Santiago (Documenta & Instrumenta - Documenta et Instrumenta, 2008)
In this article I try to call the attention on the use of the diplomatic formulae in the text of numerous medieval epigraphs. The teachers Favreau, García Lobo or Fernandez Flórez have put several times of manifest this aspect, underlining the existence of collections of diplomatic formulae used by the authors of the medieval inscriptions of diverse type and category. I will try to underline some of these parallelisms between the latin formulae of some hispanic inscriptions and those of certain contemporary documents, for which I will present diverse examples of epigraphic texts, with his equivalence in documentary texts